Change of ionized calcium level in the first 48 hours of age of preterm newborns administered with two different dosages of intravenous calcium gluconate - Anton Wibowo; Dedi Rachmadi Sambas; Abdurachman Sukadi (Indonesian Pediatric Society Publishing House, 2010)
Background Physiologically, serum calcium level declines till nadir in a few hours after birth and continues for 24-48 hours. No study performed in order to know the alteration ofionized calcium level of newborn in the first 48 hours of age. The sick newborn must have parenteral calcium to avoid hypocalcemia but there is still no agreement about the dose. Objective To determine the change of ionized calcium level in the first 48 hours of age of preterm newborns administered with peripheral drip intravenous 10% calcium gluconate of2.6 mIJkg/ day and 5 mUkg/day. Methods An open labeled randomized controlled clinical trial was performed between April and June 2009. After birth blood specimen of preterms was obtained for leukocyte, platelet, magnesium, phosphorous, and ionized calcium measurements. Subjects received either 2.6 mL/kg/day or 5 mL/kg/day of peripheral drip intravenous 10% calcium gluconate immediately after birth for 48 hours. Blood specimens was obtained again on 48 hours of age for ionized calcium. This study were analyzed using repeated measures analysis of varians. Results Forty preterm newborns (20 subjects each group) were analyzed. There was no statistical difference between both doses (Factor-A) on 48 hours ionized calcium level (P=0.33) and ionized calcium level alteration based on time (Factor-B) (P=0.20). Interaction between both factors was significantly different (P=0.035). Conclusion Ionized calcium level in 48 hours of age of preterm newborn administered with both doses of 10% calcium gluconate is not different but dose of2.6 mL/kg/day yields physiologic alteration of ionized calcium level compared with 5 mL/kg/day.